(untitled) (International Journal of Occupational Safety and Health, 2022)
Introduction: Healthcare workers (HCWs) are daily exposed to HBV infections from the blood and body fluids of patients and clients they care for in the health sector. Unfortunately, many of these HCWs are not vaccinated for hepatitis B. This study aimed to assess the factors influencing knowledge of hepatitis B vaccination amongst HCWs in a rural tertiary health facility in Edo State, Southern Nigeria. Methods: A descriptive cross-sectional study design was used in this study, and data were collected using the quantitative approach. 280 HCWs were administered with pre-tested, semi-structured interviewer-administered questionnaires. The obtained data were analyzed using IBM SPSS version 21.0, and the level of significance – alpha (α) was set at 5% (0.05). Results: The mean age of HCWs was 34.90(±9.46) years. Just above half of the HCWs, 146 (52.1%), had a good knowledge of the hepatitis B (HB) vaccine. Work type (p<0.001) and category of HCWs (p<0.001) were significantly associated with the level of knowledge of hepatitis B vaccination by respondents. Conclusion: There was poor knowledge of hepatitis B vaccination amongst HCWs with work type and category of HCW as determinants. Priority should be given to ensure targeted health promotion programmes that will improve knowledge, with a view to enhance optimal uptake of hepatitis B vaccine amongst HCWs.